Analysing Influence of Product Attributes And Customer Characteristics Towards Customer’s Purchase Intention on Edible Cutlery - Ibrahim, Samy Octavio; Herliana, Sri (Journal Integration of Management Studies, 2024)
Plastic waste has become a significant threat and problem to the world, causing many environmental and ecosystem issues. Plastic pollution causes a disturbance towards habitats and interferes with natural processes, reducing the environment's ability to adapt to climate change. Indonesia consumes more than 93 million plastic straws every day, making the country the fourth largest plastic straw-consuming country in the world. Many actions have been taken to solve this problem, one of them being the introduction of edible cutleries, including edible straws. Although the market value for edible straws shows a great opportunity, predicted to reach USD 446.96 in the year 2029, a growth of 113% from 2020, several edible cutlery provider businesses have not been receiving the expected response from the market. Departing from this problem, this research was conducted to identify factors influencing a customer's purchase intention on edible cutlery products. Seventy-eight respondents who have ever consumed any edible cutlery product residing in DKI Jakarta or Kota Bandung were involved in this study. The data was gathered using an online survey in the form of a questionnaire, using Bahasa Indonesia as the survey language. The data was then analyzed by implementing multiple linear analysis methods. The result of the study indicates that psychological factors significantly and positively affect a customer's purchase intention on edible cutleries. On the other hand, product quality, product features, product style and design, cultural factors, social factors, and personal factors do not significantly affect the purchase intention of edible cutlery products of a customer. Moreover, each independent variable for this research simultaneously affects a customer's dependent variable on edible cutlery products.